Changes in the vertical distribution of leaf area enhanced light interception efficiency in maize over generations of selection. (17th April 2019) - Perez, Raphaël P.A.; Fournier, Christian; Cabrera‐Bosquet, Llorenç; Artzet, Simon; Pradal, Christophe; Brichet, Nicolas; Chen, Tsu‐Wei; Chapuis, Romain; Welcker, Claude; Tardieu, François
Abstract: Breeders select for yield, thereby indirectly selecting for traits that contribute to it. We tested if breeding has affected a range of traits involved in plant architecture and light interception, via the analysis of a panel of 60 maize hybrids released from 1950 to 2015. This was based on novel traits calculated from reconstructions derived from a phenotyping platform. The contribution of these traits to light interception was assessed in virtual field canopies composed of 3D plant reconstructions, with a model tested in a real field. Two categories of traits had different contributions to genetic progress. (a) The vertical distribution of leaf area had a high heritability and showed a marked trend over generations of selection. Leaf area tended to be located at lower positions in the canopy, thereby improving light penetration and distribution in the canopy. This potentially increased the carbon availability to ears, via the amount of light absorbed by the intermediate canopy layer. (b) Neither the horizontal distribution of leaves in the relation to plant rows nor the response of light interception to plant density showed appreciable trends with generations. Hence, among many architectural traits, the vertical distribution of leaf area was the main indirect target of selection. Abstract : Maize breeders have indirectly selected canopies that present less leaf area at the top of the canopy and more at ear level, thereby potentially improving the ear carbon nutrition.